Chemical studies towards the synthesis of janolusimide, a marine neurotoxin from janolus cristatus - Kamaruddin, Nurulhuda (2017)
Janolusimide 19 was chosen to be the synthetic target molecule due to having a unique tripeptide structure besides showing a neurotoxin activity. Our synthetic approach towards the synthesis of janolusimide involved the construction of a core lactam system derived from L-valine using EDC.HCl followed by demethylation using four different conditions. Dimethylation at C-3 position of 133 affords (5S)-3,3- dimethyl-5-isopropylpyrrolidine-2,4-dione 26 in 72% yield using TBAF as a phase transfer catalyst. In this dimethylation step, a characteristic of ambident anion also can be observed. Multiple positions of alkylation had occurred due to enolate's ambident character of which C,O-alkylated and O-alkylated side products were observed. While the effort to synthesize the dipeptide chain was carried out using aldol reaction, Nalkylation of 26 and N-acylation of a template, 2-pyrrolidinone 139 and lactam 26 with several electrophiles. Four general protocols (Method A-D) to N-acylate 2- pyrrolidinone and lactam 26 were examined. These methods can be used as an alternative method to perform N-acylation of other lactam analogues. From these steps, two main precursors 144 and 147 towards the synthesis of janolusimide were afforded. In order to carry out mono-alkylation of β-keto amide 143, monomethylation to our template 140 was performed to optimize the reaction conditions. Mono-alkylation of β-keto amide 143 was carried out using several electrophiles such as methyl iodide, benzyl bromide, isopropyl iodide and allyl bromide afforded compounds 147, 148, 149 and 150 in 85, 64, 50 and 76% yields respectively. Chemical exploration of the lactam 133 through electrophilic substitution at C-3 afforded unique compounds 151 and 152 derived from unusual bond migration. In addition, the study of ester hydrolysis of compound 143 had proven the sensitivity of amide bond towards acid and base. Meanwhile, reduction of N-acylated lactams 144 and 147 via NaBH4 affording reduced lactam adduct 155 due to the amide hydrolysis. Besides, reduction of keto compound 147 mediated by sodium triacetoxyborohydride produced the diastereomeric mixture of reduced products 156 in 14% yield.